Quality of life and depressive symptoms in Parkinson's disease - Marcos Hortes Nisihara Chagas; Rafael Faria Sanches; Vítor Tumas; Kátia Colombo Marchi; Carlos R. Tirapelli (2011)
we have recently used the 39-item Parkinson’s Disease Questionnaire (PDQ-39) and its eight dimensions and the 15-item GDS (GDS-15) to assess quality of life and depressive symptoms in PD patients, respectively. We divided the patients into two groups (PD without depression and PD with depression) according to the GDS-15 cutoff score of eight proposed for the screening of depression in PD.